Some Universals in the Book of Mormon - Sperry, Sidney B. (Journal of Book of Mormon studies, 1995)
A universal element is a succinct concept with comprehensive spiritual appeal to humanity; the Book of Mormon is itself a universal element. Among universals found in the Book of Mormon are concepts (1) that truth is given of God to all peoples; (2) of faith, in which good and evil are clearly defined in terms of opposition; (3) of the purpose of man's existence in mortality; and (4) of the importance of service given to men and God.